Dampak dan Regulasi Fintech terhadap Inklusi Keuangan di Indonesia - Miftahul Fauzi (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
The financial technology (fintech) industry in Indonesia has grown rapidly in recent years, having a significant impact on financial inclusion in the country. Fintech provides easier and faster access to financial services, especially for segments of society previously marginalized by the traditional banking system. Fintech services such as digital payments, online loans, and technology-based investments have expanded financial reach to communities in remote areas, MSMEs, and individuals with limited access to conventional banking services. However, with the rapid growth of fintech, challenges arise related to regulation and consumer protection. Inadequate regulation can lead to security risks, legal uncertainty, and potential abuse in digital financial services. Therefore, the Indonesian government has implemented various policies to regulate and supervise the fintech industry, such as the establishment of the Financial Services Authority (OJK) and Bank Indonesia (BI) as the main supervisors. This study aims to analyze the impact of fintech developments on financial inclusion in Indonesia and evaluate the effectiveness of existing regulations in protecting consumers and encouraging the growth of the fintech sector. The results of this research show that although fintech has the potential to significantly increase financial inclusion, more comprehensive regulations and strict law enforcement are needed to ensure that the benefits of fintech can be felt evenly and safely by all levels of society.